2008
DOI: 10.1107/s1600536808030869
|View full text |Cite
|
Sign up to set email alerts
|

catena-Poly[[[aquacadmium(II)]bis(μ-4-hydroxypyridine-2,6-dicarboxylato)[aquacadmium(II)]di-μ-aqua] tetrahydrate]

Abstract: The title polymeric compound, {[Cd2(C7H3NO5)2(H2O)4]·4H2O}n or {[Cd2(hypydc)2(H2O)4]·4H2O}n (where hypydcH2 is 4-hydroxy­pyridine-2,6-dicarboxylic acid), was synthesized by the reaction of cadmium(II) nitrate hexa­hydrate with 4-hydroxy­pyridine-2,6-dicarboxylic acid and propane-1,3-diamine, in a 1:2:2 molar ratio in aqueous solution. The compound is a seven-coordinate binuclear polymeric complex with distorted penta­gonal bipyramidal geometry around CdII [Cd—O = 2.247 (4)–2.474 (3) Å]. In the binuclear monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…The bond angles around cadmium­(II) ions indicate a distortion from the ideal pentagonal-bipyramidal geometry which is also reflected in the bite angles N1–Cd1–O3, N1–Cd1–O5, N2–Cd2–O8, and N2–Cd2–O10 for 1 with values in the range 67.0(1)–69.1(1)° and in the bite angles N1–Cd1–O3, N1–Cd1–O5, N2–Cd2–O9, and N2–Cd2–O11 for 2 with values in the range 66.53(8)–69.19(8)° (Table S1 in the Supporting Information). The Cd–N and Cd–O bond distances in these polymorphs (Table ) are comparable with the corresponding ones reported in the literature for related mononuclear, binuclear, , and polynuclear cadmium­(II) complexes with dipicolinic acid or with its ethyl ester or with 4-hydroxydipicolinic acid. , …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The bond angles around cadmium­(II) ions indicate a distortion from the ideal pentagonal-bipyramidal geometry which is also reflected in the bite angles N1–Cd1–O3, N1–Cd1–O5, N2–Cd2–O8, and N2–Cd2–O10 for 1 with values in the range 67.0(1)–69.1(1)° and in the bite angles N1–Cd1–O3, N1–Cd1–O5, N2–Cd2–O9, and N2–Cd2–O11 for 2 with values in the range 66.53(8)–69.19(8)° (Table S1 in the Supporting Information). The Cd–N and Cd–O bond distances in these polymorphs (Table ) are comparable with the corresponding ones reported in the literature for related mononuclear, binuclear, , and polynuclear cadmium­(II) complexes with dipicolinic acid or with its ethyl ester or with 4-hydroxydipicolinic acid. , …”
Section: Resultssupporting
confidence: 88%
“…The Cd−N and Cd−O bond distances in these polymorphs (Table 1) are comparable with the corresponding ones reported in the literature for related mononuclear, 22−30 binuclear, 20,21 and polynuclear cadmium(II) complexes with dipicolinic acid 15−17 or with its ethyl ester 43 or with 4-hydroxydipicolinic acid. 44,45 The asymmetric unit of 1 is repeated by a c glide to produce the polymeric chain extending in the [001] direction, while the asymmetric unit of 2 is repeated by a 2-fold axis to give a polymeric chain extending in the [100] direction. Even though the respective polymers are built up in crystallographically distinct manners, the pseudocentrosymmetry of the binuclear units leads to polymers which are nearly superimposable, having identical chemical connectivity (Figure 3a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Up to now, several transitionmetal complexes based on chelidamic acid have been documented, many of them containing lanthanide metals. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] At the initiation of this work, to the best of our knowledge, no proton transfer studies and complexes using this ligand with 9-aminoacridine had been reported (however as the study was being completed, three such complexes were reported, one of which is identical with the nickel complex prepared here). 20 Therefore, we selected chelidamic acid as the major ligand and 9-aminoacridine as an auxiliary (see Scheme 1) ligand for testing their reactions with some transition metal salts.…”
Section: Introductionmentioning
confidence: 99%
“…For related structures, see: Zhou et al (2003Zhou et al ( , 2007; Ramos Silva et al (2008); Aghabozorg, Ilaie et al (2008); Aghabozorg, Manteghi & Sheshmani (2008); ; ; King et al (2005); Lin et al (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…There are several reports on coordination of 4-hydroxypyridine-2,6-dicarboxylic acid (H 3 chel or chelidamic acid) to metals, such as Fe(Hchel)Cl(H 2 O) 2 ]. (18-crown-6).2H 2 O (Zhou et al, 2007), [Zn(Hchel) Zhou et al, 2003), (tataH) 2 [Cu(Hchel) 2 .6H 2 O (tata: 2,4,6-triamino-1,3,5-triazine) (Ramos Silva et al, 2008), (Aghabozorg, Ilaie et al, 2008) [Cu(Hchel)(phen)(H 2 O)].4.5H 2 O (phen: phenanthroline) Aghabozorg, Manteghi & Sheshmani, 2008). Also, there are some reports on 2,9-dimethyl-1,10-phenanthroline (dmp) coordinated to metallic ions like (King et al., 2005) and [Cu(HCO 2 ) 2 (dmp)(H 2 O)] (Lin et al, 2008).…”
Section: S1 Commentmentioning
confidence: 99%